Pengaruh Prinsip Konfusianisme terhadap Politik Luar Negeri Tiongkok dalam Menghadapi Gagasan Universalitas HAM Barat - Indah Gitaningrum (Indonesian Journal of International Relations, 2018)
This paper aims to describe the influence of Confucianism in China’s foreign policy concerned in the human rights issue as a counter of Western universality discourse. Since The Universal Declaration of Human Rights was ratified in 1948, all nations have committed to agree in uniformity and implement it into action in the name of human rights based on the universality. The idea of Western universality always demands individual freedom and equality as a basic of human rights. This is different from the view of Confucianism which does not recognize the rights but only the obligations. Instead of individual rights, security of the community and shared prosperity are more important and must be prioritized rather than individual interests. This research uses Hobbes perspective about power relation and governance and shows that culture, ideology, and beliefs system have an important role in determining states’ foreign policies.